(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Indian independence movement, while influential across various states, had a notable impact in Karnataka, particularly in Tumkur district. Leaders of the Indian National Congress, including Tilak and Gandhiji, significantly influenced the region. After assuming leadership of the Congress, Gandhiji presided over the Belgaum session in 1924. The Tumkur Congress Committee, established in 1921, played a crucial role in the movement. Local youth, women, workers, farmers, and common people actively participated in the struggle for independence. Gandhiji visited Tumkur twice, on July 14, 1927, and January 4, 1930, during which he promoted his speeches and constructive programs. His visits deeply impacted Tumkur’s youth and Congress workers, who adopted his methods and ideologies. Prominent leaders in the district, such as K. Rangaiyangar, T. Subrahmanya, Neelkantha Rao, D. S. Mallappa, and K. Narayanshetty, were profoundly influenced by Gandhiji, maintaining continuous contact with him and embracing his principles throughout their lives.